142k views
3 votes
F(x)=4x^2+1 and g(x)=x^2-5 fins (f+g)(x)

2 Answers

3 votes
Hi there!


(f +g )(x) = f(x) +g (x)
In other words: to find (f + g)(x) we must add up the functions f(x) and g(x). Substitute both functions into the formula.


(f + g)(x) =( 4x {}^(2) + 1) + ( {x}^(2) - 5)
Remove the parenthesis, since they don't have a function in this situation.


(f + g)(x) =4x {}^(2) + 1 + {x}^(2) - 5
Rearrange the expression in order to collect terms later.


(f + g)(x) = 4x {}^(2) + {x}^(2) + 1 - 5
And finally collect the terms.


(f + g)(x) = 5x {}^(2) - 4
~ Hope this helps you!




User Daegalus
by
4.5k points
6 votes


(f+g)(x)=4x^2+1+x^2-5=5x^2-4

User Khaja Mohammed
by
6.1k points